STUDI DESKRIPTIF ANSAMBEL MUSIK KOLINTANG SEBAGAI PENGIRING NYANYIAN PADA UPACARA BENDERA DI SMP SW. ST. PAULUS SIDIKALANG - Aprilia Dame Christanty Sihombing (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
This endeed of  research is to describe the place of the kolintang music ensemble to accompany the singin of the flag ceremony at SMP Sw. St. Paulus Sidikalang. This research is a qualitative descriptive research. The subject of this research is flag ceremony. The research focussed on the role of Kolintang music ensemble as song chanting. The data of the final research was obtained from the observations of the flag-raising activities, interview with teachers, student adan kolintang’s players in junior high school and take a documentation. Data were analyzed with qualitative descriptive analysis techniques. Data validity is obtained through data triangulation, observer triangulation, theory triangulation and method triangulation. The purpose of this research is to know and descriebing  kolintang music. Example, in this research is by using numbered data such as document, archieves, interview results, observation result or also by interviewing more thn one subject that is consideret to have a different point of view.The result showed that : (1) In accompaniying singing at the flag-ceremony, students used the basic notes G, C and F. (2) the tecnic to performed kolintang    were not wheeled with a kolintang played general. (3). After carrying out their duties as chanting accompaniment in the ceremony, students who performed kolintang first practice on kolintang extracurricular activities. (4) in the process of playing kolintang, each player must have a strong feeling so that the technic kolintang is harmonious. Keywords : Descriptive Study, Ensemble, Kolintang music